Hubungan antara Hotspot Dan Kebakaran Terhadap Timbulnya Penyakit Infeksi Saluran Pernapasan Akut (ISPA) di Kabupaten Kubu Raya, Kalimantan Barat - Bambang Hero Saharjo; Denada Ramadhania (Jurnal Silvikultur Tropika, 2019)
Kalimantan is one of the Islands that often have forest and land fires where almost the entire province of Borneo ever burning. This negatively impact to the environment and human beings. This study aims to measure the correlation between distribution of hotspots as a sign of forest and land fire with the onset of Acute Respiratory Infections. In this study, was conducted a descriptive analysis on the improvement of the health impact which is limited to Acute Respiratory Infections based on age and gender. The highest amount of hotspots is in subdistrict of Sungai Raya about 144 hotspots, whereas the lowest amount of hotspots is in the Sub District of Sungai Kakap 8 hotspots. Sub-district which have the widest acreage burned was Batu Ampar sub-district which reach 5 881.46 hectares, whereas the slightest acreage burned was in subdistrict of Sungai Kakap, about 4.18 hectares have been burned. The largest amount of sufferers of ISPA patients were in district of Sungai Raya, about 11 302 patients, whereas the lowest amount of sufferers of Acute Respiratory Infections patients were in the Teluk Pakedai Sub-district that is about 1129 sufferers of Acute Respiratory Infections patients. Result of statistical analysis showed the amount of sufferers patients with the amount of Hotspots has positive correlation (r = 0.507). The value of the correlation between the amount of Acute Respiratory Infections patients with burning land area also has a positive correlation (r = 0.377). As for the correlation between the amount of hotspots with acreage burned has a positive correlation (r = 0.938). The result of R square trial obtained regression equation Y = 2 240 + 19.3 X which is not relevant to be used in determining the correlation between the increase of Acute Respiratory Infections patients with amount of hotspots. The most Patient of Acute Respiratory Infections in Kubu Raya found on classes age 1-4 years old and based on the type of gender, the difference in the amount of patients between men and women do not indicate significant differences. Key words: Acute Respiratory Infections (ARI), Forest and Land Fires, Hotspot, West Kalimantan